2015
DOI: 10.1016/j.puhe.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Is sense of coherence a predictor of lifestyle changes in subjects at risk for type 2 diabetes?

Abstract: High SOC scores were good predictors of successful lifestyle change in subjects at risk of type 2 diabetes. SOC-13 can be used in daily practice to increase clinical awareness on the impact of mastery on the outcome of life-style intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 38 publications
2
22
2
5
Order By: Relevance
“…Nilsen et al. reported similar findings in a study sample of diabetes stage 2 patients. According to Lillefjell et al.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Nilsen et al. reported similar findings in a study sample of diabetes stage 2 patients. According to Lillefjell et al.…”
Section: Introductionsupporting
confidence: 62%
“…Even if the strong SOC sample reported higher levels of pain intensity and experienced the pain as more troublesome at the baseline, the pain experience decreased more sharply by the follow-up as compared to the weak SOC sample. Nilsen et al (12) reported similar findings in a study sample of diabetes stage 2 patients. According to Lillefjell et al (11), it is important to increase SOC levels, as well as resources that encourage SOC, in those who are most vulnerable.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Strengthening the sense of coherence for individuals in need, could play a role in trying to help them handle type 2 diabetes risk [17]. Focusing on and assessing sense of coherence may be useful in improving the outcome of lifestyle interventions [16]. Individuals with few available resources could be in need of more intensive follow-up from health personnel to help them make lifestyle changes than those with more resources.…”
Section: Discussionmentioning
confidence: 99%
“…A high sense of coherence is associated with better future health [14, 15]. In individuals at risk for type 2 diabetes, a high sense of coherence is found to be associated with lifestyle change [16]. However, such associations are contested.…”
Section: Introductionmentioning
confidence: 99%